The Influence of Financial Literacy and Personality Traits on Retirement Planning Strategies Among Full-time Employees of Indonesia - Rian Ashari; Fendi Fendi; May Goverish; Silvia Sri Mustika (Syntax Idea)
The purpose of this paper is to examine the impact of financial literacy and Personality traits on retirement planning strategy among full-time employee in Indonesia. This study applies a quantitative approach and the data were collected through online survey and compose of 358 respondents of full-time employess in Indonesia. The study reveals that age, income, and openness significantly related to pursuing active planning retirement strategy. Financial knowledge and behavior do not significantly affect the intention to pursue any retirement planning strategy. We expect this study to contribute into significant implication for Goverment, financial practitioners advisor, financial services authority (OJK) & Banking regulations include an individual worker. Earlier research on retirement planning focused on financial characteristics of the individual separately from the individual’s subjective norms (age, income, dependents, personality traits). This study combine those factors and see how each factor influences the final retirement planning strategies